Golden Arches Going Green: The Impact of McDonald’s Sustainability Achievements on Public Image - Lee, Yong Yu; Kee, Daisy Mui Hung; Neng Ang, Vernoon Wei; Vadhi Vehlan, Laneishwar A/L Sri Satthian; Lee, Li Xin; Lee, See Ming; Ardel, Muhammad Raid (Advances in Global Economics and Business Journal, 2024)
This paper analyzes the correlation between McDonald's sustainability achievements and its public image. Despite receiving criticism for its environmental and social impact, McDonald's has recently made notable progress in sustainability by setting targets to source sustainable coffee, palm oil, and fish, as well as reducing greenhouse gas emissions. By utilizing a quantitative approach involving 108 customer surveys, this study investigates the influence of McDonald's sustainability achievements on its public image. The survey results reveal that respondents who were aware of McDonald's sustainability efforts exhibited a more favorable perception of the company. This study concludes that McDonald's sustainability endeavors have contributed to its environmental and social responsibility objectives while enhancing its reputation among stakeholders. Moreover, the research findings shed light on the factors that affect sustainability perception and the public image of fast-food brands. Furthermore, it calls for future research to explore the impact of cultural factors and stakeholder perspectives on the public image of fast-food chains. The findings offer valuable insights into the potential advantages of sustainability initiatives for companies aiming to improve their public image and foster consumer trust